Law Enforcement Against Domestic Violence in the Gorontalo Police Area - Saleh, Muhammad Arief; Lahaling, Hijrah; Insani, Nur (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Domestic violence (KDRT) is a human rights violation that has a serious impact on victims, especially women and children. Although it has been regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence, the implementation of law enforcement in various regions still faces various challenges. This study aims to analyze the form of law enforcement for domestic violence cases in the jurisdiction of the Gorontalo Police, as well as identify the inhibiting and supporting factors in the law enforcement process. The research method used is empirical juridical, with a qualitative approach involving interviews with law enforcement officials, victims, and accompanying institutions. The results of the study show that although the Gorontalo Police have tried to handle domestic violence cases seriously, there are still obstacles such as lack of reports from victims, patriarchal culture, limited resources, and lack of public understanding of victims' rights. This study recommends increasing the capacity of law enforcement officials, cross-sectoral cooperation, and legal education to the public to realize more effective protection for victims of domestic violence.